Chromosome Mapping of Retrotransposable Elements Rex1 and Rex3 in Three Fish Species in the Subfamily Hypoptopomatinae (Teleostei, Siluriformes, Loricariidae) - Ferreira, D. C. [UNESP]; Oliveira, C. [UNESP]; Foresti, Fausto [UNESP] (Karger, 2010)
Transposons and retrotransposons represent a great portion of the eukaryotic genome. These repeated elements can be defined as genetic entities capable of self-inserting into different positions within the genome modifying the functions of the genes with which they are associated. The purpose of the present work was to isolate, identify, and map the sequences of Rex1 and Rex3 transposable elements present in the genomes of fishes of the family Loricariidae. The retrotransposable elements were identified through amplification with Rex1 and Rex3 primers, and the nucleotide composition of the retrotransposons was determined by automatic sequencing. In all the species analyzed it was possible to isolate Rex1 partial sequences from 520 to 563 bp in size and Rex3 partial sequences from 407 to 454 bp in size. Comparisons with the available literature showed that Loricariidae retrotransposons Rex1 and Rex3 have a high sequence similarity to putative homologous genes in different fish orders. Fluorescence in situ hybridization experiments conducted in 3 species, Hisonotus leucofrenatus, Pseudotocinclus tietensis, and Parotocinclus maculicauda, using the retrotransposable elements isolated for each species as probes, revealed that Rex1 and Rex3 share a similar dispersion pattern and are both found on all chromosomes of the 3 species organized in small clusters and dispersed on all the chromosomes, including euchromatic and heterochromatic regions, although a larger concentration was observed in the heterochromatic regions of H. leucofrenatus. The data found in the present study contradict much of the literature that substantiates that the retrotranspon elements are preferentially accumulated in the heterochromatin regions in fishes. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Fluorescent in situ hybridization; Genome; Heterochromatin; Hypoptopomatinae; Retrotransposons